Hierarchical ZnO nanostructures: Growth mechanisms and surface correlated photoluminescence - Grinblat, Gustavo Sergio (2012)
ZnO nanowires were grown by vapor-transport and deposition on Au nanocluster covered fused and thermal silica and c-Si. The nanowire size and density depended strongly on the substrate type. By decreasing the O2 to local Zn partial pressure ratio, the growth pattern changed to nanocombs and nanosheets. ZnO nanohedgehogs were found on bare c-Si. We observe a remarkable correlation between the defect to exciton photoluminescence intensity ratio and the nanostructures specific surface areas. These results indicate that changes in strain and O deficiency defects at surfaces are behind the observed morphology changes, one to two-dimensional growth transition, and corresponding luminescence.